1995
DOI: 10.1074/jbc.270.46.27495
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of Type I Collagen to Lymphocyte Function-associated Antigen (LFA) 1 Integrin Triggers the Respiratory Burst of Human Polymorphonuclear Neutrophils

Abstract: The transduction pathways depending on the ␣ L ␤ 2 integrin do not involve a G protein (ruled out by the use of cholera and pertussis toxins), whereas the cytoskeleton was found to participate in the process, as evidenced by inhibition by cytochalasin B. After collagen stimulation, cytoplasmic inositol trisphosphate and calcium ion increased sharply for less than 2 min. The use of the inhibitors staurosporine and calphostin C demonstrated that protein kinase C was involved. Evaluation of the activity of this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 34 publications
(27 reference statements)
6
46
1
Order By: Relevance
“…During these processes, cells exchange various messages, principally through cytokine production, some of them being triggered by interactions with ECM proteins, that in turn lead to the maintenance of an inflammatory state or, on the contrary, to the restoration of physiological conditions. Previous works of our laboratory have shown that type I collagen was able to deeply influence the metabolism of cells involved in these processes, in the case of fibroblasts (22,23) as well as PMNs (3)(4)(5)(6). In this work, we present new evidences that type I collagen interactions with monocytes are critical events involved in these processes.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…During these processes, cells exchange various messages, principally through cytokine production, some of them being triggered by interactions with ECM proteins, that in turn lead to the maintenance of an inflammatory state or, on the contrary, to the restoration of physiological conditions. Previous works of our laboratory have shown that type I collagen was able to deeply influence the metabolism of cells involved in these processes, in the case of fibroblasts (22,23) as well as PMNs (3)(4)(5)(6). In this work, we present new evidences that type I collagen interactions with monocytes are critical events involved in these processes.…”
Section: Discussionsupporting
confidence: 53%
“…When monocytes were incubated with anti-CD11a, anti-CD11b, or anti-lymphocyte (used as additional control) Abs, which are blocking Abs (6), no inhibition of collagen I-induced O 2 Ϫ production was noticed. In the same way, the mAb anti-CD29 (␤ 1 subunit) had no effect.…”
Section: Effects Of Mabs On Monocyte O 2 ϫ Production Triggered By Acmentioning
confidence: 99%
“…A number of studies have demonstrated that "outside in" LFA-1 activation and signaling are dependent on conformational changes induced in the I-domain as a result of interaction with a ligand [35,38,48]. These activation events, including phosphorylation of exposed tyrosine residues on the CD18 cytoplasmic tail and intracellular calcium elevation [16], have also been shown to be elicited in bovine leukocytes after exposure to LktA [22]. Stabilizing the I-domain in a closed conformation with a variety of statin-derived and non-statin small molecule compounds has been shown to allosterically inhibit ligand interaction and activation of LFA-1 [25,53,54].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that type I collagen binds to CD11a/CD18 molecules, and that it triggers a respiratory burst in human neutrophils [42]. Although the binding sites have not been identified, type IV collagen also binds to neutrophils, causing inhibition of fMLP-induced, phorbol myristate acetate-induced, or type I collagen-induced activation of the cells [43].…”
Section: Discussionmentioning
confidence: 99%